Natural Radioactivity in Farmland Soils and Soil-to-Cereal Transfer of Primordial Radionuclides in Chikun Local Government Area, Kaduna State, Nigeria (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Radionuclides that are naturally present in agricultural soils have the potential to spread to food crops and provide a route for radiation exposure to humans. In Chikun Local Government Area, Kaduna State, Nigeria, this study assessed the activity concentrations of 40K, 226Ra, and 232Th in farming soils and their transfer to certain cereal crops. Four farming villages (Kujama, Rido, KRPC Perimeter, and Sabon Tasha) provided samples of composite soil and related cereal crops (sorghum, millet, and maize). Gamma-ray spectroscopy was used to measure radioactive activity concentrations, and soil-to-cereal transfer factors (TFs) were computed to evaluate radionuclide uptake. Spatial and crop-related changes were assessed using descriptive statistics and one-way analysis of variance (ANOVA). With activity concentrations ranging from 365.24 ± 28.61 to 421.68 ± 34.92 Bq kg⁻¹, the data indicated that the most common radionuclide in the soils was 40K. This was followed by 232Th (46.53 ± 7.85–58.91 ± 9.36 Bq kg⁻¹) and 226Ra (31.82 ± 5.74–41.76 ± 7.63 Bq kg⁻¹). Geological enrichment was suggested by the fact that 232Th surpassed the global norm, although 40K and 226Ra were generally within the global reference range. The order of the soil-to-cereal transfer factors was 40K > 226Ra > 232Th, with maize showing the lowest radioactive uptake and sorghum the highest. Significant variations in transfer factors across cereal crops (40K: p = 0.012; 226Ra: p = 0.021; 232Th: p = 0.038) and radionuclide activity concentrations among sampling locations (40K: p = 0.014; 226Ra: p = 0.028; 232Th: p = 0.007) were found using one-way ANOVA. The data reveal that local geology greatly influences radioactive distribution and that radionuclide transmission to cereals is crop-dependent. The produced baseline data are useful for radiological risk assessment, environmental radioactivity monitoring, and the creation of evidence-based plans to guarantee food safety and sustainable agricultural output in the research region.